Customized template for occlusal correction in full mouth rehabilitation: A case report - Tamizhesai Balavadivel; Venkateshwaran Rajendran; Karthik Ramakrishnan; Jeffin Jacob; Marion Sarah Philip; Nithiyarajan Nambirajan (Wolters Kluwer Medknow Publications, 2020)
Reestablishing the occlusal plane involves multidisciplinary approach with extensive restorative procedure to accomplish "equilibration." Broadrick occlusal plane analyzer (BOPA) provides an easy and practical method to commensurate for curve of Spee and establishing the occlusal plane. Transferring the new occlusal plane from the diagnostic model to patients mouth needs to be precise. To achieve controlled conservative reduction, customized acrylic template was a vital tool used in this case to transfer the exact plane correction achieved by the BOPA.